2005
DOI: 10.1088/0960-1317/15/10/007
|View full text |Cite
|
Sign up to set email alerts
|

Micro throttle pump employing displacement amplification in an elastomeric substrate

Abstract: We report a micro throttle pump (MTP) with enhanced throttling resulting from beneficial deformation of its elastomer substrate. In the MTP reported, this has doubled the effective deflection of the piezo electric (PZT) actuator with a consequent five-fold enhancement of throttling ratio. This mode of throttling has been modelled by finite element method and computational fluid dynamic techniques whose predictions agreed well with experimental data from a throttle test structure; providing typical throttling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Initial variants of the microthrottle pumps incorporated a defined pump chamber with throttles constricting normal to the axis of compression. 22 Subsequent developments included the use of throttles constricting parallel to the axis of compression implemented within double depth structure, 22 providing enhanced throttling ratios via displacement amplification, 20 effects within pump chambers as reported by Andersson et al 25 The resulting linear microthrottle pumps ͑LMTP͒ demonstrated pumping rates up to 1.4 ml min −1 and the ability to pump against a back pressure of 35 kPa of water. 21…”
Section: Microthrottle Pumpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial variants of the microthrottle pumps incorporated a defined pump chamber with throttles constricting normal to the axis of compression. 22 Subsequent developments included the use of throttles constricting parallel to the axis of compression implemented within double depth structure, 22 providing enhanced throttling ratios via displacement amplification, 20 effects within pump chambers as reported by Andersson et al 25 The resulting linear microthrottle pumps ͑LMTP͒ demonstrated pumping rates up to 1.4 ml min −1 and the ability to pump against a back pressure of 35 kPa of water. 21…”
Section: Microthrottle Pumpsmentioning
confidence: 99%
“…21 However, despite their modest ratios, relative to conventional, fully closing valves, pumps incorporating a pair of such throttles demonstrate pumping efficiencies close to those of micropumps incorporating conventional, fully closing valves. 20 In addition, as a result of the lack of full throttle closure, pumps utilizing microthrottles have been demonstrated to be tolerant of high particle concentrations 22 and are not affected by interfacial stiction, which is commonly exhibited if polydimethylsiloxane ͑PDMS͒ contacts another surface, 23 and are therefore capable of operating at high actuator frequencies ͑ca. 1800 Hz͒, in the context of PDMS devices.…”
Section: B Microthrottle and Mtp Operating Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow rate is inversely proportional to the fourth power of the hydraulic radius of a microchannel, so even a small reduction in a channel's cross-sectional area can produce a significant increase in flow resistance and consequently a drop in flow rate. Tan and coworkers reported the development of a microthrottling pump (MTP) [80][81][82] that manipulated the flow resistance using a pair of microthrottles molded into a PDMS substrate. An offset in PZT disk placement with respect to the throttles results in bimorphic flexion of the glass diaphragm such that the throttles operate out of phase from one another.…”
Section: Piezoelectric Micropumpsmentioning
confidence: 99%
“…Diverse micropump technologies and working principles have been introduced in previous reports 5–10 and these can be classified according to the installation location (internal vs. external pumps) and pumping schemes 11 (mechanical vs. non-mechanical or passive vs. active pump). For instance, electro-wetting technology 12 was well developed as a fluid transporting method, which can be integrated with any microfluidic system without any external fluidic connections.…”
Section: Introductionmentioning
confidence: 99%